2016
DOI: 10.1007/s11661-016-3590-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Pore Fraction Hot Tearing Model to Directionally Solidified and Direct Chill Cast Aluminum Alloys

Abstract: Hot tearing is strongly linked with the applied semi-solid strain rate. This defect is commonly qualitatively predicted using a pressure drop equation in the mushy zone that includes the effects of both tensile deformation perpendicular to the thermal gradient and shrinkage feeding. In this study, the effect of strain rate parallel to the thermal gradient is additionally introduced in order to assess its effect on hot tearing predictions. The deformation and shrinkage pore fractions are obtained on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the deformation of solids usually does not only occur in the same direction. Thus, Dou [15] introduced a strain perpendicular to the thermal gradient direction to extend the solid deformation to two dimensions. However, a certain difference between this and the deformation that occurs in three-dimensional space remains.…”
Section: Improved Rdg Criteriamentioning
confidence: 99%
“…However, the deformation of solids usually does not only occur in the same direction. Thus, Dou [15] introduced a strain perpendicular to the thermal gradient direction to extend the solid deformation to two dimensions. However, a certain difference between this and the deformation that occurs in three-dimensional space remains.…”
Section: Improved Rdg Criteriamentioning
confidence: 99%
“…Monroe and Beckermann [14,15] predicted hot tearing tendency of alloys using a dimensionless Niyama criterion, the results indicated that deformation pores under tension can result in the increase of the quantity and the volume of shrinkage pores, thus increasing the hot tearing tendency of alloys. Dou and Phillion [16] added the strain rate parallel with the thermal gradient to a pressure drop equation on the basis of the dimensionless Niyama criterion, which demonstrated that an increase in casting speed increased both the deformation and shrinkage pore fractions, resulting in an increase in the probability of hot tearing. The studies above show that the heterogeneous defects in casting have significant impact on the formation and propagation of hot tearing, which is an important factor needed to be considered in hot tearing analysis.…”
Section: Introductionmentioning
confidence: 99%